"She Deserved It": Effects of Sexism Norms, Type of Violence, and Victim's Pre-Assault Behavior on Blame Attributions Toward Female Victims and Approval of the Aggressor's Behavior. (April 2014) - Koepke, Sabrina; Eyssel, Friederike; Bohner, Gerd
Effects of ambivalent sexism, sexism norms, victim behavior, and type of violence on male students' reactions to male violence against women in intimate relationships were examined. Participants judged a scenario depicting an act of sexual or non-sexual violence against a female partner who had either shown overtly sexual or non-sexual behavior toward another man. Generally, high (vs. low) hostile sexism, high (vs. low) hostile sexism norm feedback, and victim's overtly sexual (vs. non-sexual) behavior led to stronger victim blame and perceived approval of the aggressor's behavior. The victim of non-sexual violence was blamed more than the rape victim, particularly if she had behaved in an overtly sexual manner.